Quality of Service, Efficiency, and Scale in Network Industries: An Analysis of European Electricity Distribution - Christian Growitsch; Tooraj Jamasb; Michael G. Pollitt (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2005)
Quality of service is of major economic significance in natural monopoly infrastructure industries and is increasingly addressed in regulatory schemes. However, this important aspect is generally not reflected in efficiency analysis of these industries. In this paper we present an efficiency analysis of electricity distribution networks using a sample of about 500 electricity distribution utilities from seven European countries. We apply the stochastic frontier analysis (SFA) method on multi-output translog input distance function models to estimate cost and scale efficiency with and without incorporating quality of service. We show that introducing the quality dimension into the analysis affects estimated efficiency significantly. In contrast to previous research, smaller utilities seem to indicate lower technical efficiency when incorporating quality. We also show that incorporating quality of service does not alter scale economy measures. Our results emphasise that quality of service should be an integrated part of efficiency analysis and incentive regulation regimes, as well as in the economic review of market concentration in regulated natural monopolies.
urn:nbn:de:gbv:3:2-5250
Keywords: L94; L51; L15; 330; efficiency; quality of service; scale economies; input distance function; stochastic frontier analysis; Elektrizitätswirtschaft; Produktqualität; Skalenertrag; EU-Staaten